2023
DOI: 10.1021/jacs.2c11531
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Investigation of the Rate of Intersystem Crossing in the Strong Exciton–Photon Coupling Regime

Abstract: Strong interactions between excitons and photons lead to the formation of exciton-polaritons, which possess completely different properties compared to their constituents. The polaritons are created by incorporating a material in an optical cavity where the electromagnetic field is tightly confined. Over the last few years, the relaxation of polaritonic states has been shown to enable a new kind of energy transfer event, which is efficient at length scales substantially larger than the typical Förster radius.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Coupling of vibrational excitations to infrared cavities has led to dramatic changes in thermal reaction rates. The influence of optical polaritons on photochemical processes has received comparatively less attention. Although some works show negligible changes in photophysics due to strong coupling, , other studies of optical cavities have demonstrated polaritonic effects on spin or energy conversion processes such as intersystem crossing, triplet–triplet annihilation, resonant energy transfer, delayed fluorescence, and photobleaching. …”
Section: Introductionmentioning
confidence: 99%
“…Coupling of vibrational excitations to infrared cavities has led to dramatic changes in thermal reaction rates. The influence of optical polaritons on photochemical processes has received comparatively less attention. Although some works show negligible changes in photophysics due to strong coupling, , other studies of optical cavities have demonstrated polaritonic effects on spin or energy conversion processes such as intersystem crossing, triplet–triplet annihilation, resonant energy transfer, delayed fluorescence, and photobleaching. …”
Section: Introductionmentioning
confidence: 99%
“…In polaritonic chemistry, depending on whether the quantized cavity modes are coupled via their characteristic frequencies to electronic or vibrational degrees of freedom of molecules, the situation is described as electronic-strong coupling (ESC) or vibrational-strong coupling (VSC), respectively. Under ESC, it becomes possible to modify the photochemistry/photophysics of molecules including charge transfer processes and electronic spectroscopy, and photoinduced reactions can be influenced. Similarly, for VSC, the vibrational spectra of molecules are altered by the formation of light–matter hybrid states, and even the chemical reactivity of the ground state can be modified. , , The observed effects of molecular ESC and VSC are often discussed phenomenologically, and understanding of the underlying microscopic and macroscopic physical mechanisms, especially with respect to the effects of VSC, is still incomplete. , In our recent work we have shown numerically that the interaction between an optical cavity and ensembles of molecules not only leads to cavity detuning and a change of the optical length but also allows for a local molecular polarization mechanism under strong collective vibrational coupling in the thermodynamic limit. The interplay of microscopic and macroscopic polarization is due to cavity-mediated dipole–dipole interaction.…”
mentioning
confidence: 99%
“…The population density thus have a tendency to redistribute toward low k ∥ through the exciton reservoir. Such a redistribution can be simulated using rate-equations where the lower polariton branch is approximated by a discrete set of states (Figure e) . Due to redistribution, it also sometimes happens that the emission from the lower polariton is a little bit blue-shifted as compared to polariton absorption.…”
Section: The Fabry–perot Cavitymentioning
confidence: 99%
“…Such a redistribution can be simulated using rate-equations where the lower polariton branch is approximated by a discrete set of states ( Figure 5 e). 157 Due to redistribution, it also sometimes happens that the emission from the lower polariton is a little bit blue-shifted as compared to polariton absorption. The proposed mechanism for this commonly observed phenomenon involves polariton to exciton reservoir energy transfer, followed by absorption of thermal energy and return to the lower polariton.…”
Section: The Fabry–perot Cavitymentioning
confidence: 99%